So, It’s Pricier Than Before, but Why? Price Increase Justifications Influence Risky Decision Making and Emotional Response - Salcedo, Juan C.; Jiménez-Leal, William (Frontiers in Psychology, 2019)
In this paper we investigated how justifications for price increases are associated with risky decision making and emotional responses. Across two studies with paired lottery choices and sequential decisions, we found that participants presented with a justification for price increases based on increasing demand decided to invest in a comparatively riskier asset more often than participants presented with a justification for price increases based on increasing tax or those presented with no justification at all. We also found that participants presented with justifications for price increases based on increasing demand also reported more arousal displayed higher galvanic skin response than people in the other two justification conditions. Together, these studies provide evidence that the sole increasing demand underlying a price increase of a risky asset can influence the decision to buy it and suggests that emotional activation is involved in such a decision process.